If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3=t-11/2
We move all terms to the left:
3-(t-11/2)=0
We add all the numbers together, and all the variables
-(+t-11/2)+3=0
We get rid of parentheses
-t+3+11/2=0
We multiply all the terms by the denominator
-t*2+11+3*2=0
We add all the numbers together, and all the variables
-t*2+17=0
Wy multiply elements
-2t+17=0
We move all terms containing t to the left, all other terms to the right
-2t=-17
t=-17/-2
t=8+1/2
| 4(2y-5)=-4 | | d+7/3=3 | | 3.2x+6=10 | | z+7/1=2 | | 3x-15/9=57/4 | | u-12/3=2 | | G(-3)=3x2-3x | | g+3/3=4 | | F(4)=-5x+2 | | 1=v-92/5 | | 7x+4=3x-40 | | 200m-100m+57,000=60,900-200m | | 2+14n=0 | | x/1210=2.15 | | 19=3-2y | | 3(r-13)+2=20 | | r+5/3=1 | | 2b^2+17b=-21 | | 3x-8x=4-19 | | 2.3*x=6.9 | | (7x−5)+(5x+27)=90 | | 3(x-2)-(3x+2)=5(4x+4) | | 2=15-7/8x | | 8+6u=5u | | 10n=120n=10 | | 600=2(300-x)+2x | | 32+22.18=46.75+18.24x | | -z-z-6=8 | | -10+5a=25 | | -2x-1=(1)/(2)x+1 | | 3x-(2x+14)=-19 | | X(x)=15x-56 |